Infiltration and runoff of water in soils of a basin, in southern Mexico - Lozano-Trejo, Salvador; Olazo Aquino, Jaime; Pérez-León, María Isabel; Castañeda-Hidalgo, Ernesto; Díaz-Zorrilla, Gustavo Omar; Santiago-Martínez, Gisela Margarita (REVISTA TERRA LATINOAMERICANA, 2020)
Changes in the land use of a basin area affects the infiltration and surface water runoff directly, altering the balance of the hydrological cycle. Therefore, estimating parameters of water infiltration and runoff for each type of land use and vegetation (USV) is fundamental to differentiate the impact caused by a change of land use over the hydrical balance of a given area. The objective of this study was to estimate cumulative inf iltration (F), basic inf iltration rate (Ti), constant inf iltration rate (fc) and inf iltration decay coeff icient (k); as well as inf iltration and runoff coefficients in mountainous cloud forest (BMM), (SMSPC), pine-oak forest (BPQ), oak forest (BQ), induced grassland (PI), pine forest (BP), agricultural land in use (TC) and fallowed agricultural land (TCD). Thirty-eight simulated rain experiments were carried out at an average intensity of 100 mm h-1 with a hand-portable single nozzle rainfall simulator. The exponential model was employed to estimate fc and k and the Horton semi-empirical model to estimate Ti and F. The analysis of variance was performed by the generalized linear model (GML) to evaluate the effects of USV and texture type, and the analysis of covariance was employed to determine the effects of slope, mulch depth, organic matter % of total variability content, sand, mud and clay content, and bulk density. The exponential model fitted more than 80% of total variability (R2) at all USV. Agricultural land in use and TCD showed the lowest F and Ti and the highest k (P < 0.001), BMM exhibited the highest infiltration capacity (F) and lowest decay rate (k). The bulk density of the soil, and content of mud and organic matter were the variables positively associated to infiltration (P < 0.01).